2020
DOI: 10.1007/s40204-020-00139-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the formulation of PLGA microparticles for controlled drug delivery

Abstract: Polymeric microparticles (MPs) are recognized as very popular carriers to increase the bioavailability and bio-distribution of both lipophilic and hydrophilic drugs. Among different kinds of polymers, poly-(lactic-co-glycolic acid) (PLGA) is one of the most accepted materials for this purpose, because of its biodegradability (due to the presence of ester linkages that are degraded by hydrolysis in aqueous environments) and safety (PLGA is a Food and Drug Administration (FDA)-approved compound). Moreover, its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 162 publications
4
121
0
1
Order By: Relevance
“…When composite microparticles were prepared with a variable composition of PLGA and poly-L-lactide (PLLA), it was found that 36–48% of DOX was released within the first half hour followed by slower release monitored over a period of 12.5 days [ 71 ]. Additional features of the use of PLGA microparticles in drug delivery and release have recently been reviewed [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…When composite microparticles were prepared with a variable composition of PLGA and poly-L-lactide (PLLA), it was found that 36–48% of DOX was released within the first half hour followed by slower release monitored over a period of 12.5 days [ 71 ]. Additional features of the use of PLGA microparticles in drug delivery and release have recently been reviewed [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here we used the PLGA polymer, a copolymer of lactic and glycolic acids, which is completely biocompatible and biodegradable and degrades to lactic and glycolic acids which are presented in the organism, thereby causing negligible side effects. It is worth noting that PLGA has already been approved by the FDA for therapeutic use in humans —there are more than fifteen PLGA-based formulations for the treatment of numerous disorders [ 31 , 32 ]. PLGA is one of the most popular polymers for the synthesis of nanoparticles with a therapeutic payload [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the TQ compound was encapsulated with polymeric PLGA-PEG and Pluronics F68 by a emulsion-solvent evaporation technique. This technique is the most common method used to encapsulate hydrophobic compounds [33]. TQ was dissolved in dichloromethane (DCM), incorporated with polymeric PLGA-PEG and dispersed in Pluronics F68 aqueous solution.…”
Section: Discussionmentioning
confidence: 99%